The contribution of estuary‐resident life histories to the return of adult Oncorhynchus kisutch. Issue 1 (28th April 2014) - Jones, K. K.; Cornwell, T. J.; Bottom, D. L.; Campbell, L. A.; Stein, S.
<x xml:space="preserve">Abstract</x> This study evaluated estuarine habitat use, life‐history composition, growth and survival of four successive broods of coho salmon Oncoryhnchus kisutch in Salmon River, Oregon, U.S.A. Subyearling and yearling O. kisutch used restored and natural estuarine wetlands, particularly in the spring and winter. Stream‐reared yearling smolts spent an average of 2 weeks in the estuary growing rapidly before entering the ocean. Emergent fry also entered the estuary in the spring, and some resided in a tidal marsh throughout the summer, even as salinities increased to > 20. A significant portion of the summer stream‐resident population of juvenile O. kisutch migrated out of the catchment in the autumn and winter and used estuary wetlands and adjacent streams as alternative winter‐rearing habitats until the spring when they entered the ocean as yearling smolts. Passive integrated transponder (PIT) tag returns and juvenile life‐history reconstructions from otoliths of returning adults revealed that four juvenile life‐history types contributed to the adult population. Estuarine‐associated life‐history strategies accounted for 20–35% of the adults returning to spawn in the four brood years, indicating that a sizable proportion of the total O. kisutch production is ignored by conventional estimates based on stream habitat capacity. Juvenile O. kisutch responses to the reconnection of previously unavailable estuarine habitats have led to greater life‐history diversity in the population and reflect greater phenotypic plasticity of the species in the U.S. Pacific Northwest than previously recognized.